2023
DOI: 10.1002/btm2.10580
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ionizable lipids for aerosolizable mRNA lipid nanoparticles

Mae M. Lewis,
Melissa R. Soto,
Esther Y. Maier
et al.

Abstract: Although mRNA lipid nanoparticles (LNPs) are highly effective as vaccines, their efficacy for pulmonary delivery has not yet fully been established. A major barrier to this therapeutic goal is their instability during aerosolization for local delivery. This imparts a shear force that degrades the mRNA cargo and therefore reduces cell transfection. In addition to remaining stable upon aerosolization, mRNA LNPs must also possess the aerodynamic properties to achieve deposition in clinically relevant areas of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Multiple groups have recently used NLuc (and modified NLuc) mRNA to optimize LNP formulations, even for respiratory delivery. (6873) For instance, Lokugamage et al, optimized LNPs for nebulization using a modified NLuc reporter gene and demonstrated that their lead LNP could successfully deliver therapeutic mRNA as well. This highlighted that it is possible to replace NLuc reporter mRNA with a more clinically relevant cargo and still produce significant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple groups have recently used NLuc (and modified NLuc) mRNA to optimize LNP formulations, even for respiratory delivery. (6873) For instance, Lokugamage et al, optimized LNPs for nebulization using a modified NLuc reporter gene and demonstrated that their lead LNP could successfully deliver therapeutic mRNA as well. This highlighted that it is possible to replace NLuc reporter mRNA with a more clinically relevant cargo and still produce significant results.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared nanoluciferase mRNA (NLuc) as previously published. (73) Briefly, we created a template for NLuc mRNA encoding sequences for a T7 promoter, 5’ UTR, codon-optimized NLuc, and 3’ UTR. We synthesized mRNA using AmpliScribe™ T7-Flash Transcription Kit (Lucigen, catalog #ASF-3507) as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Starting with 43 papers that report on luciferase mRNA LNPs as of April 2023, we excluded 29 papers that either (i) added a fifth component (either for stability or targeting purposes), (ii) modified other lipid components (such as helper lipid or cholesterol), or (iii) tested only in vivo. With these exclusions, the final dataset included 2,332 LNPs from 14 different papers across 10 different labs [10][11][12][13][14][15][35][36][37][38][39][40][41][42] .…”
Section: Methodsmentioning
confidence: 99%
“…However, inhalable delivery comes with its own challenges as well, particularly relating to the aerosolization of the RNA-carrying LNPs and the successful passage of the nanostructures through the lungs' protective mucociliary clearance system. 17,18 Thus, there has been substantial research focused on designing LNPs that are capable of overcoming these obstacles and successfully transfecting the cells that make up the lung epithelium.…”
mentioning
confidence: 99%
“…Because directing LNPs into the lung epithelium via IV injection has proven to be difficult in the past, the administration of LNPs via inhalation has often been explored as a more direct alternative route of delivery. , This introduces the benefits of avoiding rapid hepatic clearance, minimizing delivery to other off-target organs and tissues, and bypassing the need for LNPs to cross the pulmonary endothelial barrier. However, inhalable delivery comes with its own challenges as well, particularly relating to the aerosolization of the RNA-carrying LNPs and the successful passage of the nanostructures through the lungs’ protective mucociliary clearance system. , Thus, there has been substantial research focused on designing LNPs that are capable of overcoming these obstacles and successfully transfecting the cells that make up the lung epithelium.…”
mentioning
confidence: 99%